Mortality inequality and its implications for retirees - Shi, J (2023)
This thesis presents four studies on mortality inequality which advance the knowledge of how lifespans differ across social groups and the implications for retirees. The first two studies are based on the concept of distributional differences and propose new methods to study mortality inequality. Specifically, Chapter 2 introduces a statistical distance index to capture the stratification of lifespans among social groups. Empirical evidence from Finland demonstrates its utility and reveals new dimensions of mortality inequalities that traditional measures obscure. Chapter 3 proposes a novel method for investigating the factors that contribute to total lifespan inequality. It finds that in the United States, while racial/ethnic differences in life expectancy contribute little to total-population-level lifespan variance, distributional differences across race/ethnicity explain one fifth of the total lifespan variance. The next two studies explore the implications of mortality inequalities for retirees. Chapter 4 models dynamic work trajectories of older US adults and presents major results of gender and educational inequalities in the United States. It shows that less-educated older adults spent less time working, which compensates for their lower longevity when compared to their more-educated counterparts. Nonetheless, educational inequality in retirement lifespan is substantial and persistent. Chapter 5 looks at how education and preretirement earnings relate to lifetime pensions from age 60 onward, as well as how mortality affects the distribution of lifetime pensions in Sweden. The results show that the greater longevity of socially advantaged groups accounts for up to one quarter of lifetime pension inequality. Chapters 4 and 5 both highlight the importance of social differences in mortality and advocate for greater emphasis on the role of mortality in high-level discussions on old-age policies.